Child management and monitoring system using bluetooth low energy - Yeo, Nicholas Kaisheng (2016)
With the advancement of technology and an increasing emphasis placed on healthcare for the aging society, many of those developments can be transferred to be applied to other areas. Fall detection have advanced in recent years to aid in the monitoring of elderly folks in countries such as United States of America. Fall detection is also useful for children. The World Health Organisation has identified falls as a serious factor of childhood injuries, and a quick response to these falls can make a difference in many lives. In recent years, the development of Bluetooth Low Energy (BLE) devices allow these devices to consume less power hence granting it a greater lifespan. Texas Instruments have a low cost sensor (SensorTag) that utilizes BLE as a means of transmission. The project hence aims to develop a Child management and monitoring system for Android using BLE as a communication medium between the central hub and the SensorTag. The system aims to actively monitor the child activity and focuses on two services- fall detection and proximity detection.